Protective Effects of Nuciferine in Middle Cerebral Artery Occlusion Rats Based on Transcriptomics - Chang Chen; Quantao Ma; Jinzhu Jiang; Tieshan Wang; Linghui Qiu; An Liu (Brain Sciences, 2022)
Middle cerebral artery occlusion (MCAO), with the characteristics of high morbidity, high recurrence rate, high mortality, and disability rate, is a typical manifestation of ischemic stroke and has become a hot research topic in the clinical field. The protective effects of nuciferine on brain injury MCAO rats were investigated and its mechanisms of actions were revealed. The MCAO rats were established by the suture method. The pathological staining of the rat brain was processed and observed, the pharmacodynamics assay of nuciferine were studied, and the gene expression regulation by nuciferine was detected by transcriptome technology. The results showed that nuciferine significantly alleviated brain damage in MCAO rats, and the transcriptomic results suggested that nuciferine could exert therapeutic effects through the regulation of lipid metabolism, including arachidonic acid metabolism, sphingolipid metabolism, the PPAR signaling pathway and other related pathways. This finding provided new perspectives on the treatment of MCAO with nuciferine and facilitates the development of novel drugs for this disease.